2018
DOI: 10.1248/bpb.b17-00371
|View full text |Cite
|
Sign up to set email alerts
|

A PPAR Pan Agonist, MHY2013 Alleviates Age-Related Hepatic Lipid Accumulation by Promoting Fatty Acid Oxidation and Suppressing Inflammation

Abstract: Nonalcoholic fatty liver disease (NAFLD) is frequently observed in obese and aged individuals. Peroxisome proliferator-activated receptors (PPARs) play a role in regulating hepatic lipid accumulation, a hallmark of NAFLD development. A PPAR pan agonist, 2-(4-(5,6-methylenedioxybenzo[d]thiazol-2-yl)-2-methylphenoxy)-2-methylpropanoic acid (MHY2013) has been shown to prevent fatty liver formation and insulin resistance in obese mice (db/db) model. However, the beneficial effects of MHY2013 in aged model remain u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…A previous study demonstrated that peroxisomal function was inversely correlated with aging [36]. Reduced ACOX1 expression and peroxisomal fatty acid β-oxidation activity have been observed in the liver of old rats [37]. In another study, Sanguino et al [38] revealed that aging strongly decreases the activity and expression of PPARα in rat liver.…”
Section: Hfd-mediated Oxidative Stressmentioning
confidence: 99%
“…A previous study demonstrated that peroxisomal function was inversely correlated with aging [36]. Reduced ACOX1 expression and peroxisomal fatty acid β-oxidation activity have been observed in the liver of old rats [37]. In another study, Sanguino et al [38] revealed that aging strongly decreases the activity and expression of PPARα in rat liver.…”
Section: Hfd-mediated Oxidative Stressmentioning
confidence: 99%
“…MHY2013 is another PPAR pan-agonist that also activates all three PPAR isotypes. In aged Sprague-Dawley (SD) rats, MHY2013 treatment improved age-related hepatic lipid accumulation, and resulted in upregulated β-oxidation signaling and lower inflammation in the liver [ 162 ]. The PPAR pan-agonist Lanifibranor (CAS ID 927961-18-0) is reportedly effective in experimental skin and lung fibrosis [ 163 , 164 ].…”
Section: Pharmacological Strategies Targeting Pparβ/δ For Nafld Trmentioning
confidence: 99%
“…The development of PPARα/γ/δ pan agonists as anti-diabetic, anti-obesity, or hypolipidemic drugs is still actively ongoing 74 , 75 . For example, IVA 337 is a potent and well-balanced pan PPAR agonist which showed promising results in vitro and in vivo and is expected to be used to treat patients with metabolic syndrome and non-alcoholic steatohepatitis 76 .…”
Section: Other Pparγ Modulators and Agonistsmentioning
confidence: 99%